What´s the Use of Wondering if He´s Good or Bad: "Carousel" and the Presentation of Domestic Violence in Musicals - Álvarez Caldas, Patricia (Investigaciones Feministas (Feminist Research), 2013)
The analysis of the 1956 film Carousel (Dir. Henry King), which was based on the 1945 play by Rodgers and Hammerstein, provides a suitable example of a musical with explicit allusions to male physical aggression over two women: the wife and the daughter. The issue of domestic violence appears, thus, in a film genre in which serious topics such as these are rarely present. The film provide an opportunity to study how the expectations and the conventions brought up by this genre are capable of shaping and transforming the presentation of Domestic Violence. Because the audience had to sympathise with the protagonists, the plot was arranged to fulfil the conventional pattern of a romantic story inducing audiences forget about the dark themes that are being portrayed on screen.